2009
DOI: 10.1111/j.1460-9568.2009.06984.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar involvement in timing accuracy of rhythmic finger movements in essential tremor

Abstract: The cerebellum is involved in the generation of essential tremor (ET) and cerebellar timing function is altered in patients with ET showing an increased variability of rhythmic hand movements. Using a sensor-engineered glove, we evaluated motor behaviour during repetitive finger tapping movements in 15 patients with ET and in 11 age- and gender-matched normal subjects. In addition, we investigated whether, in patients with ET, an inhibitory repetitive transcranial magnetic stimulation (1 Hz-rTMS) over lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 47 publications
(86 reference statements)
0
70
0
Order By: Relevance
“…Previous studies have repeatedly demonstrated that low frequency (1 Hz) rTMS over the cerebellum with 500-600 pulses can affect the contralateral motor cortex for up to 30 min [11,37]. Avanzino et al proved a positive effect on motor function for several weeks using repeated stimulation with different parameterstheta burst rTMS [19]. These results do not indicate this method to be therapeutic, due to the deterioration in the results of the nine-hole peg test.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies have repeatedly demonstrated that low frequency (1 Hz) rTMS over the cerebellum with 500-600 pulses can affect the contralateral motor cortex for up to 30 min [11,37]. Avanzino et al proved a positive effect on motor function for several weeks using repeated stimulation with different parameterstheta burst rTMS [19]. These results do not indicate this method to be therapeutic, due to the deterioration in the results of the nine-hole peg test.…”
Section: Discussionmentioning
confidence: 91%
“…Gironell et al stimulated the middle cerebellum (1 Hz, 300 pulses) in ten patients with essential tremor, observing tremor reduction 5 min after rTMS [18]. Avanzino et al evaluated motor behaviour during repetitive finger tapping movements in 15 patients with essential tremor; a 1-Hz 600-pulse rTMS stimuli over the right lateral cerebellum transiently reduced abnormal elongated touch duration values and normalized intertapping interval values [19]. Koch et al stimulated with theta burst rTMS (three-pulse bursts at 50 Hz repeated every 200 ms for 40 s, 600 pulses) over the lateral cerebellum in ten patients with advanced Parkinson's disease (PD), who had L-dopa-induced dyskinesias.…”
Section: Introductionmentioning
confidence: 97%
“…We found that there is a correlation between the extent of vermal torpedo pathology and the extent of hemispheric torpedo pathology, suggesting that these postmortem changes are not independent, but rather, that they likely reflect the presence of a common, underlying (i.e., broader) cerebellar system problem. There is a long-standing clinical literature that supports the concept that a dysfunction of the cerebellum causes ET, including the presence in ET patients of intention tremor [31,32], gait ataxia [13,33], oculomotor abnormalities [34], and problems with dysrhythmia and motor learning [35][36][37][38][39]. These findings often occur in patients with cerebellar diseases (e.g., spinocerebellar ataxia) [37,40].…”
Section: Discussionmentioning
confidence: 91%
“…It has been hypothesized that cognitive deficits are mediated through cerebellar, thalamic and frontal connections that are compromised in ET [Kim et al 2009;Troster et al 2002;Sahin et al 2006]. Much of the literature supports that ET is a disorder of cerebellar dysregulation, including the presence of intention tremor [Leegwater- Kim et al 2006;Louis et al 2009b], gait ataxia [Singer et al 1994;Stolze et al 2001], oculomotor abnormalities [Helmchen et al 2003] and problems with dysrhythmia and motor learning [Trillenberg et al 2006;Avanzino et al 2009;Bares et al 2010;Farkas et al 2006;Shill et al 2009;Kronenbuerger et al 2007]. In addition, postmortem studies in ET have indicated the presence of a variety of structural and degenerative changes in the cerebellum, including increased number of Purkinje cell axonal swellings ('torpedoes') [Louis et al 2007b;Axelrad et al 2008], increased number of displaced or heterotopic Purkinje cells [Kuo et al 2011], reduction in number of Purkinje cells in some studies [Axelrad et al 2008] [Bucher et al 1997], positron emission tomography [Jenkins et al 1993;Wills et al 1994;Colebatch et al 1990], 1 H magnetic resonance spectroscopic imaging [Louis et al 2002;Pagan et al 2003], diffusion tensor imaging [Shin et al 2008;Klein et al 2011;Nicoletti et al 2010], voxelbased morphometry [Benito-Leon et al 2009;Quattrone et al 2008] and studies using other automated volumetric methods [Cerasa et al 2009] which demonstrate the presence of functional, metabolic and structural abnormalities in the cerebellum of ET patients.…”
Section: Current Literature On the Relationships Between Et And Cognimentioning
confidence: 99%